Estimating Oil Price Volatility Using Stochastic Volatility (SV) and Its Impact on Corporate Investment - parisa Mohajeri; reza Taleblou; Fatemeh KhanAhmadi (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2022)
Firm investment is one of the important financial decisions in the economy, which affects the value of companies and the wealth of shareholders, which can result in increasing welfare. Despite neglecting the effects of uncertainty in traditional investment theories, modern theories have introduced various mechanisms for the impact of uncertainty on investment expenditures. Using the daily data of oil prices and the data of 131 companies listed on the Tehran Stock Exchange market during the period of 2008-2020, the factors affecting the investment of the companies are identified by emphasizing the oil price uncertainty. For this purpose, in the first step, the stochastic volatility model in the framework of the space-state approach is the basis for estimating the oil price uncertainty, and in the next, according to the results of the Hausman endogeneity test, the instrumental variable method is used to estimate the coefficients of the variables affecting investment. The findings indicate that first, the volatility of oil prices has no significant effect on investment. Second, firm size, profitability, inflation, and Tobin’s Q affect investment positively and significantly. Third, the financial leverage, which is reflected in the capital structure polices, has a significant negative effect on investment, meaning that more focus on debt financing leads to less corporate investment expenditures.